Exploring artificial intelligence adoption challenges: bridging the technology gap for marketing advancements - Susi Susanti Tindaon; Jonas Meylan Freddy Banurea (Institute of Advanced Engineering and Science, 2026)
Artificial intelligence (AI) holds immense potential to enhance marketing strategies for micro, small, and medium enterprises (MSMEs). However, significant barriers, including financial constraints, limited digital literacy, and inadequate government support, hinder its widespread adoption. This study compares AI adoption challenges across two Indonesian MSME ecosystems; tourism-oriented Bali and agrarian Garut using the diffusion of innovation (DOI) lens and complementary model⎯technology organization environment (TOE), technology acceptance model (TAM), unified theory of acceptance and use of technology (UTAUT). The findings reveal that MSMEs in Bali exhibit characteristics of